If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -7) = (3x + 2)(2x + 1) Reorder the terms: 3(-7 + x) = (3x + 2)(2x + 1) (-7 * 3 + x * 3) = (3x + 2)(2x + 1) (-21 + 3x) = (3x + 2)(2x + 1) Reorder the terms: -21 + 3x = (2 + 3x)(2x + 1) Reorder the terms: -21 + 3x = (2 + 3x)(1 + 2x) Multiply (2 + 3x) * (1 + 2x) -21 + 3x = (2(1 + 2x) + 3x * (1 + 2x)) -21 + 3x = ((1 * 2 + 2x * 2) + 3x * (1 + 2x)) -21 + 3x = ((2 + 4x) + 3x * (1 + 2x)) -21 + 3x = (2 + 4x + (1 * 3x + 2x * 3x)) -21 + 3x = (2 + 4x + (3x + 6x2)) Combine like terms: 4x + 3x = 7x -21 + 3x = (2 + 7x + 6x2) Solving -21 + 3x = 2 + 7x + 6x2 Solving for variable 'x'. Reorder the terms: -21 + -2 + 3x + -7x + -6x2 = 2 + 7x + 6x2 + -2 + -7x + -6x2 Combine like terms: -21 + -2 = -23 -23 + 3x + -7x + -6x2 = 2 + 7x + 6x2 + -2 + -7x + -6x2 Combine like terms: 3x + -7x = -4x -23 + -4x + -6x2 = 2 + 7x + 6x2 + -2 + -7x + -6x2 Reorder the terms: -23 + -4x + -6x2 = 2 + -2 + 7x + -7x + 6x2 + -6x2 Combine like terms: 2 + -2 = 0 -23 + -4x + -6x2 = 0 + 7x + -7x + 6x2 + -6x2 -23 + -4x + -6x2 = 7x + -7x + 6x2 + -6x2 Combine like terms: 7x + -7x = 0 -23 + -4x + -6x2 = 0 + 6x2 + -6x2 -23 + -4x + -6x2 = 6x2 + -6x2 Combine like terms: 6x2 + -6x2 = 0 -23 + -4x + -6x2 = 0 Factor out the Greatest Common Factor (GCF), '-1'. -1(23 + 4x + 6x2) = 0 Ignore the factor -1.Subproblem 1
Set the factor '(23 + 4x + 6x2)' equal to zero and attempt to solve: Simplifying 23 + 4x + 6x2 = 0 Solving 23 + 4x + 6x2 = 0 Begin completing the square. Divide all terms by 6 the coefficient of the squared term: Divide each side by '6'. 3.833333333 + 0.6666666667x + x2 = 0 Move the constant term to the right: Add '-3.833333333' to each side of the equation. 3.833333333 + 0.6666666667x + -3.833333333 + x2 = 0 + -3.833333333 Reorder the terms: 3.833333333 + -3.833333333 + 0.6666666667x + x2 = 0 + -3.833333333 Combine like terms: 3.833333333 + -3.833333333 = 0.000000000 0.000000000 + 0.6666666667x + x2 = 0 + -3.833333333 0.6666666667x + x2 = 0 + -3.833333333 Combine like terms: 0 + -3.833333333 = -3.833333333 0.6666666667x + x2 = -3.833333333 The x term is 0.6666666667x. Take half its coefficient (0.3333333334). Square it (0.1111111112) and add it to both sides. Add '0.1111111112' to each side of the equation. 0.6666666667x + 0.1111111112 + x2 = -3.833333333 + 0.1111111112 Reorder the terms: 0.1111111112 + 0.6666666667x + x2 = -3.833333333 + 0.1111111112 Combine like terms: -3.833333333 + 0.1111111112 = -3.7222222218 0.1111111112 + 0.6666666667x + x2 = -3.7222222218 Factor a perfect square on the left side: (x + 0.3333333334)(x + 0.3333333334) = -3.7222222218 Can't calculate square root of the right side. The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 2u-u= | | p/3asfdr | | w/7.5=52 | | 5n=10-5n | | 3x(2x+7)= | | 9.8/1.4 | | 3/5-x | | 8s+7=9s | | 3(2z-10)=54 | | 4z-42=32-3 | | 2(7+11)+3(7)=57 | | 7x+x(x-5)=0 | | y-(-13)=4/3(x-(-11)) | | k/7=17 | | d-3=95 | | 14x-2(9-x)=0 | | log(7)*y=5x | | 4y-13=12 | | 113=-25 | | 3(x-4)+12=14 | | 114+t-29=7t+25 | | $10.03/$29.07 | | y=-16t^2+32t+8 | | 12m+5n-4m+10n= | | x^3(-x^2)*y=363 | | 9a-3(3+2a)+3=54 | | (-2x^4)+(4x^3)-16=0 | | sin(2x)-2sin(x)=0 | | -14x+4(x-4)+9x=8x-34 | | (X+2)-3(x-3)+4(2x-7)=18 | | 5x+20=15x | | 2(2x+3)=5x-14 |